Accuracy of aging ducks in the U.S. Fish and Wildlife Service Waterfowl Parts Collection Survey - Aaron T. Pearse; Douglas H. Johnson; Kenneth D. Richkus; Frank C. Rohwer; Robert R. Cox Jr.; Paul I. Padding (Wildlife Society Bulletin)
ABSTRACT The U.S. Fish and Wildlife Service conducts an annual Waterfowl Parts Collection Survey to estimate composition of harvested waterfowl by species, sex, and age (i.e., juv or ad). The survey relies on interpretation of duck wings by a group of experienced biologists at annual meetings (hereafter, flyway wingbees). Our objectives were to estimate accuracy of age assignment at flyway wingbees and to explore how accuracy rates may influence bias of age composition estimates. We used banded mallards (Anas platyrhynchos; n = 791), wood ducks (Aix sponsa; n = 242), and blue‐winged teal (Anas discors; n = 39) harvested and donated by hunters as our source of birds used in accuracy assessments. We sent wings of donated birds to wingbees after the 2002–2003 and 2003–2004 hunting seasons and compared species, sex, and age determinations made at wingbees with our assessments based on internal and external examination of birds and corresponding banding records. Determinations of species and sex of mallards, wood ducks, and blue‐winged teal were accurate (>99%). Accuracy of aging adult mallards increased with harvest date, whereas accuracy of aging juvenile male wood ducks and juvenile blue‐winged teal decreased with harvest date. Accuracy rates were highest (96% and 95%) for adult and juvenile mallards, moderate for adult and juvenile wood ducks (92% and 92%), and lowest for adult and juvenile blue‐winged teal (84% and 82%). We used these estimates to calculate bias for all possible age compositions (0–100% proportion juv) and determined the range of age compositions estimated with acceptable levels of bias. Comparing these ranges with age compositions estimated from Parts Collection Surveys conducted from 1961 to 2008 revealed that mallard and wood duck age compositions were estimated with insignificant levels of bias in all national surveys. However, 69% of age compositions for blue‐winged teal were estimated with an unacceptable level of bias. The low preliminary accuracy rates of aging blue‐winged teal based on our limited sample suggest a more extensive accuracy assessment study may be considered for interpreting age compositions of this species. Published 2013. This article is a U.S. Government work and is in the public domain in the USA